2015
DOI: 10.1017/s0272263115000364
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Instruction, Bilingualism, and the Older Adult Learner

Abstract: Little is known about older adult language learners and effects of aging on L2 learning. This study investigated learning in older age through interactions of learner-internal and -external variables; specifically, late-learned L2 (bilingualism) and provision of grammar explanation (explicit instruction, EI). Forty-three older adults (age 60+) who were monolingual English or bilingual English/Spanish speakers learned basic Latin morphosyntax using a computer program with or without EI. Results showed no overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 45 publications
4
58
2
Order By: Relevance
“…Cox () investigated learning in older age with 43 adults aged 60+ who were either monolingual or bilingual in the United States. Using a computer program to learn basic Latin morphosyntax, with and without explicit instruction (EI), the bilinguals with EI showed advantages of transferring skills.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cox () investigated learning in older age with 43 adults aged 60+ who were either monolingual or bilingual in the United States. Using a computer program to learn basic Latin morphosyntax, with and without explicit instruction (EI), the bilinguals with EI showed advantages of transferring skills.…”
Section: Resultsmentioning
confidence: 99%
“…In support of positive aging, delaying the onset of dementia is a priority for modern societies, and the neurobiological evidence provided in the majority of these studies should empower policy makers to fund programs to support language education, particularly for senior citizens. Research that confirms the benefits of language study by senior citizens (Cox, ) speaks to the importance of funding programs, not only for Pre‐K–post‐secondary learners but also throughout the full life spectrum. Similar benefits were reported in studies that were conducted in the EU and UK on citizens who were bi‐ or multilingual and whose positive or better‐than‐expected health (attributed in part to their robust cognitive state) extended well into their later years (e.g., Perequin et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although quite a few studies suggest bilingual advantages for the functions listed above, others show no group differences (or show an advantage for monolinguals, Okita & Jun Hai, 2001), both for lexical learning (Antoniou et al, 2015; Gonzalez-Ardeo, 2000) and for preposition learning (Gibson, Hufeisen & Libben, 2001). Thus, clear conclusions are difficult to draw and more research is needed, especially with regard to the linguistic domain of grammar, which has been addressed by only three studies (Cox, 2017; Nation & McLaughlin, 1986; Nayak, Hansen, Krueger & McLaughlin, 1990). Moreover, weaknesses and gaps within these studies 1 , as well as heterogeneity across them, make the existing literature on grammar even more inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…attention switching) from which both older and younger learners can benefit (Bak, Long, Vega-Mendoza, & Sorace, 2016); such cognitive benefits have also been found in delayed post-tests after six months of intensive FL learning via computer-based language training software and computer games (Wong et al, 2019)although the opposite has also been reported (see e.g. Berggren et al, 2018;Ramos et al, 2017); (e) there are advantages in additional (instructed) language learning for late bilinguals compared to monolinguals regardless of type of instruction (Cox & Sanz, 2015;Cox, 2017);…”
Section: How Older Adults May Benefit From L2 Learningmentioning
confidence: 98%